Essays on industrial organization - Bretan, Pedro Luis Accioli Nobre (2010)
This thesis is comprised of three essays with a common goal: expand the theories about what drives the shape of an industry and its consequences. All three are theoretical and applied, in the sense of being detailed studies about the inner workings of industries and their impact on the shape of the latter. In the first chapter I model how the interplay among institutional quality, trust and contract incompleteness affects firms' decisions about their international mode of organization. Second second chapter also concerns industries' ownership choices, but in a complete different perspective, focusing in information transmission between the different parts that constitute a supply chain. Finally, third chapter uses industrial organization modeling to show how the internal structure of an industry influence the risk of payroll-backed loans.